2022
DOI: 10.3390/ijerph192214955
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Vapour Increases ACE2 and TMPRSS2 Expression in a Flavour- and Nicotine-Dependent Manner

Abstract: COVID-19 infects via the respiratory system, but it can affect multiple systems and lead to multi system failure. There is growing evidence that smoking may be associated with higher rates of COVID-19 infections and worse outcomes due to increased levels of ACE2 in lung epithelial cells, but it is unknown whether E-cigarette use may lead to increased risk of COVID-19 infection from the SARS-CoV-2 virus. In this study, healthy donor bronchial epithelial cells (NHBE) and monocyte-derived macrophages (MDM) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Compatible with this speculation, we found that the antioxidant N-acetyl cysteine attenuated PM 10 -stimualted ACE2 expression. Furthermore, we found that CSE, a known source of oxidative stress, 15 , 16 increased ACE2 expression in both A549 cells and HPNEpCs. Indeed, in HPNEpCs, CSE 5% was the more potent stimulus of ACE2 expression.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Compatible with this speculation, we found that the antioxidant N-acetyl cysteine attenuated PM 10 -stimualted ACE2 expression. Furthermore, we found that CSE, a known source of oxidative stress, 15 , 16 increased ACE2 expression in both A549 cells and HPNEpCs. Indeed, in HPNEpCs, CSE 5% was the more potent stimulus of ACE2 expression.…”
Section: Discussionmentioning
confidence: 71%
“…In this study, we sought to assess the effect of curbside PM 10 on ACE2 expression in human nasal epithelial airway cells, and in Vero-E6 cells we sought to determine whether curbside PM 10 increases susceptibility to SARS-CoV-2 infection. The effect of cigarette smoke extract (CSE) was also assessed because it is a source of oxidative stress, 15 it increases ACE2 expression in primary airway epithelial cells in vitro , 16 and ACE2 expression is increased in the lower airway of smokers. 17 …”
mentioning
confidence: 99%